The Role of App Update and User Feedback - Pramod K. Sharma,; Charu Shree,; Devendra K,; Daksh, (International Journal of Psychosocial Rehabilitation, 2020)
Developing a mobile app that users will love can be a challenging task even with a great idea and a talented development team. It’s impossible to anticipate every user’s need or preference. That’s where user feedback comes in collecting feedback from app users is essential for improving app’s functionality, user experience, and overall success. It provides us with valuable insights into what users like, what they don’t like, and what they want to see improved. In turn, this information allows us to make data-driven decisions about our app’s development. Our work explores the rule of user reviews in app updates based on release notes. For this purpose, we collected user reviews and released notes for Spotify, the number one app in the music category in apple app store, as the research data. Then, we manually removed non-informative parts of each release notes and manually determined the relevance of the app reviews with respect to the release notes. Our empirical results show that more than 60% of the matched reviews are actually irrelevant to the corresponding release notes. When zooming in at these relevant user reviews, we found that around half of them were posted before the new release and referred to requests, suggestions, and complaints. Whereas the other half of the relevant user reviews were posted after updating the apps and concentrated more on bug reports and praise.